Lauren's moving day - Sarah, Duchess of York, 1959-; Cunliffe, Ian (New York : Sterling Children's Books, 2011)
Even though Lauren is excited about her family's new house and having her own bedroom for the first time, she is anxious about the move and worried about changes. Includes ten hints for parents to help children move to a new home.
School Library Journal
School Library Journal, August 2011
2.1
K-3
K-3
Keywords: Change -- Juvenile fiction; Moving, Household -- Juvenile fiction; Change -- Fiction; Moving, Household -- Fiction; Change -- Fiction; Moving -- Fiction; Picture books for children